Anoikis resistance and oncoviruses. Issue 3 (12th September 2017) - Kakavandi, Ehsan; Shahbahrami, Ramin; Goudarzi, Hossein; Eslami, Gita; Faghihloo, Ebrahim
Abstract: Anoikis is known as a special type of programmed cell death which occurs in response to loss of correct cell‐extracellular matrix (ECM) connections. This process could be as pivotal event in normal development and tissue homeostasis and found as important mechanism in cancer invasiveness and metastasis. The persistent infection with oncoviruses including EBV (Epstein Bar virus), HPV (Human Papillomaviruses), HBV (Hepatitis B virus), KSHV (Human herpesvirus 8), HTLV‐1 (Human T‐lymphotropic virus‐1), and HCV (Hepatitis C virus) accounted as one of main risk factor for cancer progression. Some of them play critical roles in metastasis, especially in anoikis resistance which could contribute to metastasis of tumor cells. The better understanding of effects of oncoviruses on anoikis could contribute to finding of effective therapeutic platforms for treatment of virus‐associated cancers. This paper highlighted effects of these oncoviruses on anoikis protection in cancer. Abstract : Oncovirus are known types of virus which are able to induce cancerous condition in normal tissues and cells. It has been showed that these viruses could lead to induce cancer in various cell types via targeting a variety of cellular and molecular targets involve in anoikis. The identification of direct and indirect targets in anoikis pathway which are affected by oncoviruses, could contribute to more understanding of cellular and molecular pathways involve in these events and might provide new therapeutic approaches against oncoviruses. Here, in the first time, we summarized the molecular and cellular pathways involve in anoikis which targeted by oncoviruses.